1992
DOI: 10.1002/ajmg.1320430313
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial cushion defect: Further studies of “isolated” versus “syndromic” occurrence

Abstract: The isolated occurrence of endocardial cushion defect (ECD) has been suggested to differ from its occurrence within the context of a syndrome, with regard to the nature (complete or partial) of the defect and the associated cardiovascular malformations. Analysis of data derived from the Baltimore-Washington Infant Study of congenital cardiovascular malformations supports the observation that "syndromic" ECD tends to be of the complete atrioventricular canal type and is less frequently associated with left card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 18 publications
6
35
0
Order By: Relevance
“…Excluding cases with DS, the AVCD is also frequently associated with other genetic syndromes and extracardiac anomalies (Marino et al, 1990;Carmi et al, 1992;Digilio et al, 1999;Pierpont et al, 2000). We found that 87.5% of our patients with AVCD and TOF had a genetic syndrome or extracardiac anomalies.…”
Section: Genetic Syndromes and Extracardiac Malformationsmentioning
confidence: 72%
“…Excluding cases with DS, the AVCD is also frequently associated with other genetic syndromes and extracardiac anomalies (Marino et al, 1990;Carmi et al, 1992;Digilio et al, 1999;Pierpont et al, 2000). We found that 87.5% of our patients with AVCD and TOF had a genetic syndrome or extracardiac anomalies.…”
Section: Genetic Syndromes and Extracardiac Malformationsmentioning
confidence: 72%
“…Interestingly, in one of the patients presented here, the AVSD was associated with heterotaxy, including isomerism of the atria and azygos continuation as well as malrotation of the gut. This constellation of malformations is also seen in the polyasplenia syndrome, another disorder frequently associated with AVSD [Carmi et al, 1992]. It is, therefore, possible that the heart malformations seen in chromosome 8p deletions are related to a laterality defect, which can sometimes manifest only at the level of the heart [Devriendt et al, 1994].…”
Section: Discussionmentioning
confidence: 94%
“…This is the case of AVC found in Down syndrome [Marino, 19931 and deletion 8p patients [Marino et al, 1992;Digilio et al, 19931. AVC is occasionally observed also in children with other aneuploidies, including trisomy 18, trisomy 9, deletion lop and monosomy X [Carmi et al, 1992;Marino et al, 1989;1991a;Digilio et al, 19911. In addition, AVC may be a component of some mendelian disorders including Holt-Oram, Smith-Lemli-Opitz, DiGeorge syndromes, and mainly Ellis-van Creveld syndrome [Carmi et al, 1992;Marino et al, 1991b;Lynch et al, 19681.…”
Section: To the Editormentioning
confidence: 98%